TSG‐6 Is Weakly Chondroprotective in Murine OA but Does not Account for FGF2‐Mediated Joint Protection. Issue 10 (7th October 2020) - Zhu, Linyi; Donhou, Shannah; Burleigh, Annika; Miotla Zarebska, Jadwiga; Curtinha, Marcia; Parisi, Ida; Khan, Sumayya Nafisa; Dell'Accio, Francesco; Chanalaris, Anastasios; Vincent, Tonia L.
Abstract : Objective: Tumor necrosis factor α–stimulated gene 6 (TSG‐6) is an anti‐inflammatory protein highly expressed in osteoarthritis (OA), but its influence on the course of OA is unknown. Methods: Cartilage injury was assessed by murine hip avulsion or by recutting rested explants. Forty‐two previously validated injury genes were quantified by real‐time polymerase chain reaction in whole joints following destabilization of the medial meniscus (DMM) (6 hours and 7 days). Joint pathology was assessed at 8 and 12 weeks following DMM in 10‐week‐old male and female fibroblast growth factor 2 (FGF2) −/−, TSG‐6 −/−, TSG‐6 tg (overexpressing), FGF2 −/− ;TSG‐6 tg (8 weeks only) mice, as well as strain‐matched, wild‐type controls. In vivo cartilage repair was assessed 8 weeks following focal cartilage injury in TSG‐6 tg and control mice. FGF2 release following cartilage injury was measured by enzyme‐linked immunosorbent assay. Results: TSG‐6 messenger RNA upregulation was strongly FGF2‐dependent upon injury in vitro and in vivo. Fifteeen inflammatory genes were significantly increased in TSG‐6 −/− joints, including IL1 α, Ccl2, and Adamts5 compared with wild type. Six genes were significantly suppressed in TSG‐6 −/− joints including Timp1, Inhibin β A, and podoplanin (known FGF2 target genes). FGF2 release upon cartilage injury was not influenced by levels of TSG‐6. Cartilage degradation was significantly increased at 12 weeks post‐DMM in male TSG‐6 −/− mice, with a nonsignificant 30% reduction in disease seen in TSG‐6 tg mice. No differences were observed in cartilage repair between genotypes. TSG‐6 overexpression was unable to prevent accelerated OA in FGF2 −/− mice. Conclusion: TSG‐6 influences early gene regulation in the destabilized joint and exerts a modest late chondroprotective effect. Although strongly FGF2 dependent, TSG‐6 does not explain the strong chondroprotective effect of FGF2.